Fresh, chilled and post-thawed semen characteristics of Dorper rams fed with different concentrations of protein and selenium - M. R., Julie Marzlinda; H., Hazlinda; Panandam, J. M.; Alimon, A.R; S., Shanmugavelu; Yaakub, H. (MalaysianSociety of Animal Production, 2022)
This study aimed to determine the effects of different levels of protein and selenium (Se) supplementation on semen characteristics of fresh, chilled and post-thawed Dorper rams. Seventeen rams between 15 to16 months of age were used and fed on either 180 g of protein (P1) or 270 g of protein (P2); supplemented without Se (S0) or with1mg/kg of body weight; of Selemax 2000 (S1). Semen was collected using an artificial vagina and cryopreserved using a Tris-egg yolk extender. All fresh, chilled and post-thawed semen samples have been evaluated for their quality. The wave motion was observed under a phase contrast microscope and sperm motility was analysed using a CEROS sperm analyser. Eosin-nigrosin stain was used to determine sperm viability and abnormalities, while Pope's stain was to determine sperm acrosome intact. The HOST solution was to determine sperm membrane integrity. The results showed wave motion score of fresh semen in P1 was higher (P<0.05) than in P2. Meanwhile, S1 showed an increment (P<0.05) in wave motion score, total motility and acrosome integrity of fresh semen compared to S0. However, there was no significant effect on the quality of chilled semen fed with different CP and Se. Nonetheless, S1 did show lower (P>0.05) head abnormalities in post-thawed semen than S0. It was concluded that Dorper ram fed with 180g per kg/DM of protein is recommended in maintaining reproductive performances while organic Se supplementation (1 mg/kg Se) did improve head damages in fresh and post-thawed Dorper ram semen.